2021
DOI: 10.3389/fgene.2021.729768
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Significance of Long Non-coding RNA MIAT in Human Cancers: A Review and Meta-Analysis

Abstract: Background: Although the treatment of cancer has made evident progress, its morbidity and mortality are still high. A tumor marker is a critical indicator for early cancer diagnosis, and timely cancer detection can efficiently help improve the prognosis of patients. Therefore, it is necessary to identify novel markers associated with cancer. LncRNA myocardial infarction associated transcript (MIAT) is a newly identified tumor marker, and in this study, we aimed to explore the relationship between MIAT and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Increasing evidence demonstrates that lncRNAs were aberrantly expressed in a variety of malignancies, act as oncogenes or tumor suppressors based on their expression levels, and play a role in cancer development. For example, lncRNAs, such as PANDAR (31), MIAT (32), and SNHG15 (33) have been shown to be aberrantly expressed in various tumors and interrelated with the prognosis of tumor patients. Together, these findings suggested that lncRNA could be a distinct cancer prognostic biomarker and therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates that lncRNAs were aberrantly expressed in a variety of malignancies, act as oncogenes or tumor suppressors based on their expression levels, and play a role in cancer development. For example, lncRNAs, such as PANDAR (31), MIAT (32), and SNHG15 (33) have been shown to be aberrantly expressed in various tumors and interrelated with the prognosis of tumor patients. Together, these findings suggested that lncRNA could be a distinct cancer prognostic biomarker and therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on ncRNAs in human biology have gained much interest in the scientific world in recent years (Kapoor et al, 2021;Makkos et al, 2021;Wang et al, 2021). The role of ncRNAs in immune regulation, inflammation and autoimmunity can be of significant translational implication in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple meta-analyses have also demonstrated the prognostic value of other ncRNAs such as lncRNAs, circRNAs and large intergenic noncoding RNA (lincRNA) in cancer patients. For example, expression of a lncRNAs, such as nuclear paraspeckle assembly transcript 1 (NEAT1) [ 155 ], myocardial infarction associated transcript (MIAT) [ 156 ], noncoding RNA activated by DNA damage (NORAD) [ 157 ] and growth arrest-specific 5 transcript (GAS5) [ 158 ], as well as expression of circRNA, such as, ciRS-7 [ 159 ] and lincRNA-regulator of reprogramming (lincRNA-ROR) [ 160 ], have been found to be associated with overall survival of cancer patients.…”
Section: Harnessing Ncrnas To Enhance Disease Managementmentioning
confidence: 99%